Mapping Psychosocial Challenges, Mental Health Difficulties, and MHPSS Services for Unaccompanied Asylum-Seeking Children in Greece: Insights from Service Providers - Ioanna Giannopoulou; Gerasimos Papanastasatos; Eugenia Vathakou; Thalia Bellali; Konstantia Tselepi; Paraskevas Papadopoulos; Myrsini Kazakou; Danai Papadatou (Children)
Background/Objectives: Evidence-based information is crucial for policymakers and providers of mental health and psychosocial services (MHPSS) for unaccompanied asylum-seeking children (UASC). However, there is a scarcity of national-level studies investigating the MHPSS needs of UASC and how these are addressed in Greece. The research objectives of this study were to explore: (a) the psychosocial and mental health needs of UASC living in Greek long-term accommodation facilities as perceived by MHPSS providers, and (b) the range of services across the country, highlighting gaps and best practices in service delivery. Method: An exploratory, predominantly quantitative design was adopted to map UASC’s psychosocial difficulties, mental health problems, and MHPSS delivery. Purposive sampling was implemented, with 16 of 17 NGOs operating long-term accommodation facilities for UASC and 16 child and adolescent mental health services (CAMHS) participating. The sample included 79 participants (34 facility coordinators, 28 field psychologists, and 16 CAMHS directors). A 5-W mapping tool (Who, Where, What, When, and Which) was used for data collection, through an online survey. Data analysis involved quantitative and qualitative methods (content analysis). Results: Of 798 minors, almost 59% showed signs of behavioral or emotional disturbance, with over half referred for psychiatric assessment and 27.7% needing inpatient care. Aggression, disruptive behaviors, self-harm, and suicidal ideation were the most challenging issues. CAMHS directors reported a high rate of crisis-driven responses, with 42.1% of UASC needing emergency psychiatric evaluation. Psychosocial support was hindered by communication difficulties, lack of a shared care philosophy, understaffing, job insecurity, and limited resources. Conclusions: Our findings highlight the mental health needs of UASC, and the challenges faced by facility coordinators, psychologists, and community mental health specialists. Future research should focus on the institutional and organizational factors influencing service delivery to improve support for UASC.